Restrictive use of interpretation of language actions in legal construction - Romadhon, Ahmad Heru; Lapasere, Fachria; Wardantik, Yuli Endah (SAINTIS Publishing, 2022)
The purpose of this study is to understand the essence of language action in legal construction as a means of communication that should rely on language grammar in interpreting the meaning of sentences. Such a method is an attempt to avoid the different interpretations of the multiple interpretations of the meaning of language. The simplification of legal language must be linked to the content of the rules, where there are two arguments regarding